Persistent myths and misconceptions about second language acquisition: A study of English teachers in international schools in Semarang - Jafar Sodiq; Theresia Cicik Sophia Budiman; Maria Yosephin Widarti Lestari (Universitas Islam Sultan Agung, 2025)
Myths and misconceptions about Second Language Acquisition (SLA) is vital for creating effective learning environments, particularly in bilingual education settings. Many bilingual schools and early childhood education in Semarang implement the English learning in their curriculum. This research aims to describe the myths and misconceptions about the acquisition of a second language among English teachers in bilingual or international school and provide recommendations on the implementation of second language learning. This research employs the descriptive qualitative method with 17 teachers as the participants from 7 international schools in Semarang City. This study adopts a descriptive qualitative research design, aiming to explore and describe the perceptions, beliefs, and misconceptions about second language acquisition (SLA) among English teachers. The data sources include questionnaires, semi-structured interviews, and unstructured observations involving 17 teachers from 7 international schools in Semarang City and surrounding areas. The methodological approach follows Sandelowski,’s (2000) model of qualitative description, which emphasizes providing a comprehensive, low-inference summary of events or experiences in everyday terms. For the data analysis, the study uses descriptive statistical analysis for the questionnaire data and Miles and Huberman’s interactive model for qualitative data, involving data reduction, data display, interpretation, and conclusion drawing. This results, based on questionnaire responses and semi-structured interviews with teachers, revealed that many believe second language acquisition should begin early, as grammar mastery and accurate pronunciation are more easily achieved at a young age. They also hold that an effective way to learn a second language is to plunge children directly into a second language environment. In the cognitive aspect, the mastery of the second language depends on the parents’ level of English mastery. The teachers also agree that grammar is not so important for a good command of English. Further researches are needed to study the misconceptions among bilingual school administrators.